(untitled) (Journal of Computational Mathematics, 2018)
A splitting-up method, which splits the chemical kinetic terms from the flow terms, is presented to solve time-dependent, one-dimensional, laminar, premixed flame problems. An example for studying the development of an ozone decomposition flame is calculated. A movable boundary technique is adopted, so that the number of grid points can be significantly reduced. Special care is taken to maintain the accuracy of the solution. The results are checked in many ways. All checks show that the present method is satisfactory.